A purely Bayesian approach for proportional visual data modelling. (2018) - Bourouis, Sami; Laalaoui, Yacine; Bouguila, Nizar
In this paper, we focus on constructing new flexible and powerful parametric framework for proportional visual data modelling. In particular, we propose a Bayesian density estimation method based upon mixtures of scaled Dirichlet distributions. The consideration of Bayesian learning is interesting in several aspects. It allows simultaneous parameters estimation and model selection, it permits also taking uncertainty into account by introducing prior information about the parameters and it allows overcoming learning problems related to over- or under-fitting. In this work, three key issues related to the Bayesian mixture learning are addressed which are the choice of prior distributions, the estimation of the parameters, and the selection of the number of components. Moreover, a principled Metropolis-within-Gibbs sampler algorithm for scaled Dirichlet mixtures is developed. Finally, the proposed Bayesian framework is tested via two challenging real-life applications namely scene reconstruction and face age estimation from images. The obtained results show the merits of our approach.